In vitro maturation and fertilization of swamp buffalo (Bubalus bubalis) oocytes - Jainudeen, M.R.; Takahashi, Y.; M., Nihayah; Kanagawa, H. (Elsevier Science B.V., 1993)
Cumulus-oocyte complexes (COC) collected at slaughter from adult (n=4) and gonadotrophin-treated prepuberal (n=4) swamp buffaloes were matured in TCM199 with fetal calf serum (FCS), antibiotics and hormones (follicle stimulating hormone (FSH) and E2), at 39°C in 5% CO2 and 95% air for 24 h. Freshly collected buffalo semen was diluted with defined medium (DM) containing 5 mg ml-1 bovine calf serum (BSA), and washed by centrifugation. COC were co-incubated with sperm for 24 h in DM supplemented with heparin and theophylline. Oocytes were then examined for fertilization after fixation and staining with orcein. The numbers of COC harvested were 29 35 and 29 39 for adults and prepuberal ovaries, respectively. The maturation rates were 41% ( 12 29) and 52% ( 15 29), and fertilization rates were 21% ( 6 29) and 21% ( 6 29) for adult and prepuberal buffaloes, respectively. Two out of nine inseminated oocytes co-cultured with oviductal cells developed into morulae 6 days following in vitro insemination. It is concluded that swamp buffalo oocytes can be fertilized in vitro and the prepuberal buffalo could serve as a potential oocyte donor.